Pengembangan Formula Biofungisida dan Aplikasinya dalam Mengendalikan Penyakit Layu Fusarium pada Tanaman Tomat (Solanum lycopersicum L.) - SITUMORANG, DONI; KHALIMI, KHAMDAN; PHABIOLA, TRISNA AGUNG (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.4, Oktober 2021, 2021)
Development of a Biofungicide Formula and Its Application in Controlling Fusarium Wilt in Tomato Plants ( Solanum lycopersicum L .) Fusarium oxysporum fsp. lycopersici is one of the pathogenic fungi that causes Fusarium wilt disease in tomato plants and is very detrimental in tomato cultivation. Fusarium wilt disease control can be done by using a biofungicide formula that does not damage the environment. Biofungicide is the use of biological agents as active ingredients combined with natural carrier agents to form a biofungicide formula. The fungus Gliocladium sp. is a biological agent that can be used as an active ingredient in a biofungicide formula. This study aims to test the ability of Gliocladium sp. in inhibiting the growth of the fungus F. oxysporum fsp. licopersici in vitro and tested the ability of the formula with the active ingredient Gliocladium sp. in suppressing the incidence of wilt disease in vivo. The results of the inhibitory test of Gliocladium sp. against the growth of the fungus F.oxysporum fsp . lycopersici showed that the treatment of Gliocladium sp. can suppress the growth of fungal colonies F. oxysporum fsp. lycopersici with the percentage of inhibition of 99.21%. Testing of biofungicide formulas in vivo shows that the four biofungicide formulas namely F1, F2, F3 and F4 are able to control Fusarium wilt disease in tomato plants with a wilt disease percentage of 0%.